Attachment in Middle Childhood: Associations With Information Processing. Issue 148 (June 2015) - Zimmermann, Peter; Iwanski, Alexandra
Abstract: Attachment theory suggests that internal working models of self and significant others influence adjustment during development by controlling information processing and self‐regulation. We provide a conceptual overview on possible mechanisms linking attachment and information processing and review the current literature in middle childhood. Finally, we discuss and suggest future directions for research in this field. © 2015 Wiley Periodicals, Inc.